Nineteenth International Seaweed Symposium
DOI: 10.1007/978-1-4020-9619-8_34
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of seaweeds in the laying hen ration to improve the quality of n-3 fatty acid enriched eggs

Abstract: An association between dietary fish oil and decreased yolk weight and reduced sensory quality of eggs has been reported when eggs are enriched with n-3 FA from fish oil. Seaweeds are an important source of compounds that seem to increase egg weight when included in the laying hen diet. The objectives of this study were to determine the influence of the dietary seaweeds Macrocystis pyrifera, Sargassum sinicola and Enteromorpha sp. on the physical quality, lipid composition and consumer acceptability of n-3 FA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
10

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 17 publications
3
25
0
10
Order By: Relevance
“…The authors observed that the content of linolenic acid and docosahexaenoic acid increased in the egg yolk. Similar results were found by using Spirulina microalgae instead of Chlorella microalgae [108].…”
Section: Microalgae As Foodsupporting
confidence: 86%
“…The authors observed that the content of linolenic acid and docosahexaenoic acid increased in the egg yolk. Similar results were found by using Spirulina microalgae instead of Chlorella microalgae [108].…”
Section: Microalgae As Foodsupporting
confidence: 86%
“…High nÀ3 PUFAs content is an important feature of Ulva products, which has been used, for example, to improve egg quality through n3 PUFAs enrichment by feeding leghorn hens with a diet supplemented with sardine oil and Enteromorpha spp. (Carrillo et al, 2008). Although U. clathrata presented low lipid content, its high PUFA content is superior to those of the terrestrial vegetables and indicates its potential utilisation in preparation of human foods.…”
Section: Lipids and Fatty Acidsmentioning
confidence: 95%
“…Recently, the effects of spirulina supplementation on animal performance and quality of animal products have been examined in the diets of dairy cows (Simkus et al, 2007;Christaki et al, 2012), fattening lambs (EL-Sabagh et al, 2014), rabbits (Colla et al, 2008;Peiretti & Meineri, 2008;Gerencser et al, 2014), common carp (Abdulrahman & Hamad Ameed, 2014), pigs (Grinsteal et al, 2000), laying hens (Carrillo et al, 2008;Maries et al, 2012;Zahroojian et al, 2013) and broilers (Ross & Dominy, 1990;Toyomizu et al, 2001;Alvarenga et al, 2011;Bellof & Alarcon, 2013). Nevertheless, published data could not be found on the effects of dietary spirulina on chicken meat oxidative stability and fatty acid profile.…”
Section: Introductionmentioning
confidence: 99%